Nerve growth factor against PTSD symptoms: Preventing the impaired hippocampal cytoarchitectures. (January 2020) - Feng, Da-Yun; Guo, Bao-Lin; Liu, Gao-Hua; Xu, Ke; Yang, Jing; Tao, Kai; Huang, Jing; Wang, Li-Ying; Wang, Wen; Wu, Sheng-Xi
Highlights: The therapeutic effect of NGF on PTSD and underlying cytological mechanism was not fully elucidated so far. Feng et al reported that NGF treatment ameliorated the modified single prolonged stress induced PTSD-like symptoms. NGF prevented the impaired hippocampal cytoarchitectures via the TrkA-ERK-CREB pathway. Abstract: Although exogenous nerve growth factor (NGF) demonstrated great potential for post-traumatic stress disorder (PTSD) treatment, its therapeutic effect and underlying cytological mechanism were not fully elucidated so far. We employed a controlled, prospectively designed modified single prolonged stress mice model to investigate the role of exogenous NGF on the modified single prolonged stress induced PTSD-like symptoms and hippocampal cytoarchitecture impairment, as well as the potential neuronal signaling modulation. We discovered that the modified single prolonged stress-exposure induced significant PTSD-like symptoms as well as mildly impaired hippocampal Cornu Ammonis 1 (CA1) subregion cytoarchitecture, but not dentate gyrus neurogenesis, together with a gradual inhibition of TrkA-CREB-ERK signalings in hippocampal CA1 subregion. NGF treatment dose-dependently ameliorated the modified single prolonged stress induced PTSD-like symptoms. NGF increased the cytoplasm/nucleus ratio and improved the neuronal plasticity, mainly via the TrkA-ERK-CREB pathway. Our study offered the translational evidence for the potential application of exogenous NGF for treating or early preventing PTSD after stress exposure.